Mass media performance in Malaysia's 1990 general elections: lessons and predictions for 1995 / Sankaran Ramanathan - Ramanathan, Sankaran (Faculty of Communication and Media Studies (FCMS), 1994)
This chapter begins with an overview of major political development in Malaysia in the period 1986 to 1990. It then discourses the 1990 general elections focusing on the findings of the research project vis-à-vis the role of the media. The final section draws some lessons and makes some predictions for the forthcoming 1996 general elections.